Cross-Cultural Differences in Adopting Social Cognitive Career Theory at Student Employability in PLS-SEM: The Mediating Roles of Self-Efficacy and Deep Approach to Learning - Zhao, Wen-Xuan; Peng, Michael Yao-Ping; Liu, Fang (Frontiers in Psychology, 2021)
Unable to keep pace with the expectations of employers and societies that are constantly changing around the world, higher education policy and talent training have given rise to a gap between university education and employment. However, the higher education and industrial needs derived from technological progress have changed the country development. This study aims to verify the learning method of Taiwanese versus Malaysian university students and examines the relationship between teacher knowledge transfer and student employability from a social cognitive career theory perspective. In this study, a total of 619 Taiwanese questionnaires and 443 Malaysian questionnaires were collected to compare the two sample groups in the development of student employability. The results indicate that teacher knowledge transfer has significant positive correlations with self-efficacy and a deep approach to learning and student employability, and that self-efficacy and a deep approach to learning have significant positive correlations with student employability in the Taiwanese sample. In Malaysia, except for the path between teacher knowledge transfer and student employability, all paths were significant and positively related. Finally, according to our results and findings, this study proposes several insights with practical and theoretical implications for future study.